Effect of Black Cardamom Extracts on Mutans Streptococci in Comparison to Chlorhexidine Gluconate and De-ionized Water (In Vitro Study) - Khalil, Sara I.; Al-Obaidi, Wesal A.; Ali, Wifaq M. (Journal of Baghdad College of Dentistry, 2016)
Background: Spices and herbs have been used by many cultures to enhance the flavor and aroma of food and for their medicinal value. Black cardamom is one of these spices widely used in cooking because of its unique taste and powerful flavor. The aim of study was to test the effect of black cardamom on Mutans Streptococci in comparison to chlorhexidine gluconate (0.2%) and de-ionized water.Materials and methods: Dried fruits of black cardamom were extracted by using alcohol (70% ethanol). Saliva was collected from seven volunteers. Agar well technique with different concentrations of black cardamom extracts was used to test the sensitivities of Mutans Streptococci, as well black cardamom extracts effect on viable counts of Mutans Streptococci.Results: Mutans Streptococci was sensitive to different concentrations of alcohol extracts of black cardamom in vitro starting with (5%) to (40%) using agar well diffusion technique. Black cardamom was effective in inhibition of Mutans Streptococci but still weaker than chlorhexidine gluconate 0.2%. Highly significant reduction in the counts of bacteria was reported with cardamom extracts and CHX in comparison to neutral control after 2 hrs.Conclusions: Black cardamom showed an effect on Mutans Streptococci but still less than CHX.